Pengaruh Service Excellence Terhadap Kepuasan Nasabah Bank Syariah Dengan Harapan Nasabah Sebagai Variabel Moderasi - Mufita Rahmatul Barokah; Rahmawati Khoiriyah (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
The development of Islamic banking in the Greater Solo area reflects positive dynamics, but changes in customer behavior and the need for digitalization emphasize the need to improve service quality. This study aims to (1) Empirically test the effect of Service Excellence on Customer Satisfaction (2) Analyze the relationship between Customer Expectations and Customer Satisfaction (3) Test the moderating role of Customer Expectations in assessing the extent to which these variables can strengthen or weaken the relationship between Service Excellence and Customer Satisfaction. The research approach applied a quantitative method with a causality design. Primary data was obtained through an online questionnaire administered to 200 active Islamic bank customers in Greater Solo who had interacted with Customer Service. The analysis was conducted using PLS-SEM. The findings revealed that Service Excellence had a positive effect on Customer Satisfaction, with the attitude dimension being the strongest indicator. Conversely, Customer Expectations did not show a significant relationship with Customer Satisfaction and did not act as a moderator in the relationship between Service Excellence and Customer Satisfaction. This conclusion reinforces that customer satisfaction is determined more by actual service experience than by initial expectations. This study suggests that Islamic banks should focus on improving the attitude and responsiveness dimensions of customer service rather than simply manipulating customer expectations through marketing communications.